Effects of three rainfall patterns on soil chemical properties in black pepper cultivation in a hilly topography - Abd Hamid @ Ghazali, Izzah; Wan Yahaya, Wan Asrina; Abd Wahid, Samsuri; Idris, Wan Mohd Razi; Vijayanathan, Jeyanny (Universiti Putra Malaysia Press, 2021)
This study was conducted to determine the effect of the rainfall pattern on cation nutrients in black pepper cultivation in a hilly topography. A field study was conducted in black pepper cultivation in a hilly topography around Bintulu, Sarawak, Malaysia, with a 26o slope during the Northeast monsoon in 2020. Six blocks were established on 462.56 m2, with four subsequent soil samples (0-20 cm) collected per block after the rainfall. Soil samples were analysed using the standard pH, total organic carbon (TOC), soil texture, total nitrogen (TN), available phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), iron (Fe), and manganese (Mn) in triplicate. Rainfall pattern (October < November > December) affects TN (300.31-1422.90 mg/kg) and K availability (13.54-166.68 mg/kg), especially during peak season in November 2020. Available P, Ca, Mg, Fe, and Mn exhibit minimum rainfall effect but are closely related to combined interaction with parent material and topography. Therefore, proper soil management, such as applying fertiliser using top dressing, foliar spray, and manure amendment, including growing cover crop, is recommended to improve nutrient availability.